Legislative instability and achieving a legal security approach in the field of investment - Houchat, Fouzia (Journal of Human Sciences, 2023)
The study of the investment climate requires verifying the suitability of the legal environment capable of providing the necessary conditions that allow the investor to safely istablish his projects, and because Algeria is among the countries hosting foreign investments, the legislator has tried to provide a comprehensive and complete legal system that contains all the guarantees, but the changes The amendments and even repeals that affected the investment law, have greatly affected the stability of laws. These circumstances have led to a decline in investment in Algeria as a result of legal insecurity.